PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KONERJA INDUSTRI KECIL DAN MENENGAH (IKM) IRMA SASIRANGAN DI BANJARMASIN - Sulastini Sulastini (Center for Study and Journal Management FTI UMI, 2019)
This study aims to test and explain the Effect of Competence and Work Environment on Employee Performance of IKM Sasirangan in Banjarmasin and Banjarbaru. This research was applied to the Small and Medium Industry Sector (IKM) sasirangan. A sample of 52 respondents was determined by Saturated Sampling techniques. Data collection is done through observation, questionnaires and interviews. The method used is a quantitative approach (positivism), because the data obtained from the survey results in the form of numbers are then analyzed using statistics to answer questions and test the research hypothesis. The data analysis technique uses multiple linear regression equation analysis methods. This study aims to examine and explain the significant effect of competence partially on employee work. Test and explain the significant effect of the work environment partially on employee performance. Testing and explaining the significant influence of competencies and work environment simultaneously on employee performance. The population in this study are individual employees who are still actively working on SMIs, all employees in the Small and Medium Industry Sector (IKM) sasirangan.Partial testing The influence of Competency Variables (X1) on employee performance is 6.67. Thus, the hypothesis that competency has a positive and significant effect on employee performance in the Small and Medium Industry Sector (IKM) has proven to be accepted. The influence of work environment variables (X2) on employee performance is 16.30. Thus partially the environment has a significant influence on the performance of employees in the Small and Medium Industry Sector, IKM, as proven to be accepted. Influence of Competence and Work Environment simultaneously on employee performance. The value of t count is 73.547. Thus simultaneously having a significant effect on the performance of employees in the Small and Medium Industry Sector (IKM) sasirangan proved to be accepted. These results indicate that the competency and work environment owned by the IKM sasirangan owners can improve the performance of SMIs